Microglia promote glioblastoma via mTOR‐mediated immunosuppression of the tumour microenvironment. (22nd June 2020) - Dumas, Anaelle A; Pomella, Nicola; Rosser, Gabriel; Guglielmi, Loredana; Vinel, Claire; Millner, Thomas O; Rees, Jeremy; Aley, Natasha; Sheer, Denise; Wei, Jun; Marisetty, Anantha; Heimberger, Amy B; et al.
Abstract: Tumour‐associated microglia/macrophages (TAM) are the most numerous non‐neoplastic populations in the tumour microenvironment in glioblastoma multiforme (GBM), the most common malignant brain tumour in adulthood. The mTOR pathway, an important regulator of cell survival/proliferation, is upregulated in GBM, but little is known about the potential role of this pathway in TAM. Here, we show that GBM‐initiating cells induce mTOR signalling in the microglia but not bone marrow‐derived macrophages in both in vitro and in vivo GBM mouse models. mTOR‐dependent regulation of STAT3 and NF‐κB activity promotes an immunosuppressive microglial phenotype. This hinders effector T‐cell infiltration, proliferation and immune reactivity, thereby contributing to tumour immune evasion and promoting tumour growth in mouse models. The translational value of our results is demonstrated in whole transcriptome datasets of human GBM and in a novel in vitro model, whereby expanded‐potential stem cells (EPSC)‐derived microglia‐like cells are conditioned by syngeneic patient‐derived GBM‐initiating cells. These results raise the possibility that microglia could be the primary target of mTOR inhibition, rather than the intrinsic tumour cells in GBM. Synopsis: Using glioblastoma multiforme (GBM) mouse models and human in vitro assays, this study identifies the mTOR pathway in microglia as a major regulator of immune evasion in the tumour stroma, pointing to a need for cell‐targeted therapeutic approaches in brain malignancies. GBM patient‐conditioned medium increases mTOR signalling in microglia but not bone‐marrow‐derived macrophages. Genetic mTORC1 inactivation in microglia reduces tumour growth in vivo . Microglial mTORC1 promotes STAT3‐mediated secretion of anti‐inflammatory cytokines and limits peripheral T cell infiltration. Syngeneic GBM‐conditioned media deregulates mTOR signaling in human PSC‐derived microglial‐like cells. Abstract : GBM‐induced stromal mTORC1 mediates immune evasion by shifting inflammatory cytokine secretion.